Hybrid diamond/ carbon fiber microelectrodes enable multimodal electrical/chemical neural interfacing. (February 2020) - Hejazi, Maryam A.; Tong, Wei; Stacey, Alastair; Soto-Breceda, Artemio; Ibbotson, Michael R.; Yunzab, Molis; Maturana, Matias I.; Almasi, Ali; Jung, Young Jun; Sun, Shi; Meffin, Hamish; Fang, Jian; et al.
Abstract: Implantable medical devices are now in regular use to treat or ameliorate medical conditions, including movement disorders, chronic pain, cardiac arrhythmias, and hearing or vision loss. Aside from offering alternatives to pharmaceuticals, one major advantage of device therapy is the potential to monitor treatment efficacy, disease progression, and perhaps begin to uncover elusive mechanisms of diseases pathology. In an ideal system, neural stimulation, neural recording, and electrochemical sensing would be conducted by the same electrode in the same anatomical region. Carbon fiber (CF) microelectrodes are the appropriate size to achieve this goal and have shown excellent performance, in vivo . Their electrochemical properties, however, are not suitable for neural stimulation and electrochemical sensing. Here, we present a method to deposit high surface area conducting diamond on CF microelectrodes. This unique hybrid microelectrode is capable of recording single-neuron action potentials, delivering effective electrical stimulation pulses, and exhibits excellent electrochemical dopamine detection. Such electrodes are needed for the next generation of miniaturized, closed-loop implants that can self-tune therapies by monitoring both electrophysiological and biochemical biomarkers.